The coach in a MegaEvent: the construction of the Luiz Felipe Scolari persona at the 2014 World Cup - Filipe Mostaro; Milene Gomes Ferreira Mostaro (Eracle)
Mega-events are important spaces for the construction of narratives, influencing social, cultural, economic, political and technological aspects. In this article, we analyze how the newspaper “O Globo” narrated the career of Luiz Felipe Scolari, coach of the Brazilian national team, during the 2014 World Cup. The analysis considered editions from the day after the call-up, the day of the first game and the day after the semi-final against Germany. We focused on reports in which the Brazilian national team was the main topic, investigating how Scolari was represented. “O Globo”, as part of the largest media conglomerate in Brazil, plays an important role in the construction of identities linked to soccer. The results show that the newspaper’s assessment of the coach was directly influenced by the team’s performance: until the defeat to Germany, the stories were positive, but after the result, they all became negative, revealing a clear link between the result and the narrative.